PERAN KYAI SEBAGAI PEMIMPIN INFORMAL DALAM PERUBAHAN SOSIAL MASYARAKAT DESA PEMATANG KECAMATAN KRAGILAN KABUPATEN SERANG - Ade Millatus Sa’adiyyah; Ibnu Wijaya Kusuma (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
This research is titled The Role of Kyai as Informal Leader in Social Change in Pematang Village Community, Kragilan District, Serang Regency which is based on the social changes in the village community amid the community that is indeed associated with the existence of an informal leader. The purpose of this study is to find out how the role played by the kyai figure as an informal leader can play a role in the social change of the village community. The research method used is descriptive analysis research with a qualitative approach, the data source in this study can be processed by extracting information/information directly from information sources that are considered to be related to this research. The results of this study can find out how the role played by Kyai as an informal leader in social change in rural communities which certainly can be proven from the results of research achievements. The conclusion of this study is the figure of Kyai as an informal leader who is in the middle